Eye Gaze and Interaction Differences of Holistic Versus Analytic Users in Image-Recognition Human Interaction Proof Schemes - Leonidou, Pantelitsa; Constantinides, Argyris; Belk, Marios; Fidas, Christos; Pitsillides, Andreas (My University, 2021)
Image-recognition Human Interaction Proof (HIP) schemes are widely used security defense mechanisms that are utilized by service providers to determine whether a human user is interacting with their system and not malicious software. Inspired by recent research, which underpins the necessity for designing user-centered HIPs, this paper examines, in the frame of an accredited cognitive style theory (Field Dependence-Independence – FD-I), whether human cognitive differences in visual information processing affect users’ visual behavior when interacting with an image-recognition HIP challenge. For doing so, we conducted an eye tracking study (n = 46) in which users solved an image-recognition HIP challenge. Analysis of users’ interactions and eye gaze data revealed differences in users’ visual behavior and interactions between Holistic and Analytic users within image-recognition HIP tasks. Findings underpin the added value of considering users’ cognitive processing differences in the design of adaptive and adaptable HIP security schemes.
Keywords: Eye tracking study; Human cognitive differences; Human interaction proof schemes; Image-recognition CAPTCHA